Adaptation and Resilience: A Narrative Study on Grit among Santri in Pesantren Environments - Achmad Ali Reza; Nadia Aulia Nadhirah (The Institute of Research and Service Community IPMAFA Pati, 2025)
This study explores the development of grit among santri (students) in pesantren environments through a qualitative narrative approach. The study employed narrative interviews with three santri (E, F, H), and the data were analysed using thematic narrative analysis to capture developmental patterns of perseverance. Grit—defined as passion and perseverance for long-term goals—was examined across participants' lived experiences. Findings reveal a five-stage process: orientation (intrinsic motivation, spiritual drive), complication (emotional pressure, adaptation crises), effort (coping strategies, social support), resolution (perspective shifts, self-acceptance), and evaluation (reflection on resilience). The results highlight grit as a dynamic process shaped by initial motivation, social interactions, spiritual values, and identity reconstruction. The study underscores pesantren environments as transformative spaces that foster character development through adaptive challenges, reinforcing long-term resilience.